Variasi Jumlah Sudu Impeller Terhadap Kinerja Mini Pompa Sentrifugal - anwar, zainuri; Mardiana; Imam Rifa'i, Ahmad (JURNAL UNITEK, 2025)
The performance of a centrifugal pump is influenced by the design of the impeller, one of which is the number of impeller blades. The objective of this study is to determine the optimal impeller blade number geometry for a centrifugal pump. The type of impeller used is a backward-curved radial impeller with variations in the number of blades: 5, 6, 7, and 8. The impeller and pump casing were fabricated using a 3D printing machine with PLA filament material. The results of the study show that the highest pump discharge occurred with 8 blades, reaching a flow rate of 41.34 liters per minute at a speed of 2541 rpm, with a pump efficiency of 33.69%. The greater the number of blades, the higher the efficiency and capacity of the pump. However, this condition needs to be further reviewed for additional blade numbers to determine the optimal impeller geometry for centrifugal pump design.